Visualizing morphological principles for efficient photocurrent generation in organic non-fullerene acceptor blends [Research data] - Köntges, Wolfgang; Perkhun, Pavlo; Kammerer, Jochen; Alkarsifi, Riva; Würfel, Uli; Margeat, Olivier; Videlot-Ackermann, Christine; Simon, Jean-Jacques; Schröder, Rasmus R.; Ackermann, Jörg; Pfannmöller, Martin (Universität, 2022)
Research Data associated with the related publication.